Aktivitas antioksidan, total fenolik, flavonoid dan saponin anggur laut (Caulerpa lentillifera) diekstrak dengan pelarut yang berbeda polaritas - Andarini Diharmi; Edison Edison; Mirna Ilza; Dahlia Dahlia; Reza Saputra (AGROINTEK, 2024)
Caulerpa lentillfera is a species of seaweed that belongs to the class Chlorophyceae (green seaweed). Caulerpa lentillifera contains secondary metabolites consisting of alkaloids, flavonoids, steroids, terpenoids, saponins and phenols that can be used as antioxidants, antimicrobials, anticancer and others.  This study was aimed to determine the total phenolic flavonoid compounds, saponins, and antioxidant activity of Caulerpa lentillifera extract. The research method used is an experiment by conducting a series of experiments, namely the extraction of Caulerpa lentillifera using the maceration method in stages with solvents of different polarity. The solvents used consisted of non-polar (n-hexane), semi-polar (ethyl acetate) and polar (methanol).  The analysis parameters consisted of yield analysis, total phenol, flavonoid, saponin, and antioxidant activity.  The yield of Caulerpa lentillifera extract extracted with n-hexane, ethyl acetate, and methanol was 0.36; 0.39; and 0.42%.  The content of saponins produced from hexane, ethyl acetate and methanol extracts were 0.14%; 0.17%; and 0.20%, respectively, in a 100 g sample.  The total phenol produced in the ethyl acetate and methanol extracts were 141,50 mgGAE/100 g and 154,65 mg GAE/100 g, respectively.  Flavonoid content was 116,82 mg QE/100 g only found in methanol extract.  The antioxidant activity of n-hexane, ethyl acetate, and methanol extracts with IC50 values were 234.28, 203.96, and 124,77 ppm, respectively.  Extracts of Caulerpa lentillifera with different polarity solvents were produced different bioactive components. Saponins were produced in all three types of solvents, phenol  were found in ethyl acetate and methanol extracts and flavonoids only in methanol extract. The highest antioxidant activity of Caulerpa lentillifera was produced with methanol extract with IC 50 value of 124,77 ppm.